Effect of Dietary Supplement of Algae (Spirulina platensis) as an Alternative to Antibiotics on Growth Performance and Health Status of Broiler Chickens - Rubel , Md. Zahir Uddin; Beg, Md. AnwarulHaque; Islam, K.B.M. Saiful; Begum, Maksuda; Patoary, Md. Mahfuj Ullah (International Journal of Poultry Science, 2019)
Objective: The aim of the current study was to evaluate the effects of adding Spirulina platensis as a dried powder to the commercial broiler feed on the growth performance, microbial population in the excreta and biochemical and hematological parameters of broiler chicks in comparison to an antibiotic-based diet. Materials and Methods: A total of 150 one-day-old broiler chicks (Cobb 500) were used in a 28-day experiment. Broiler chicks were allocated to five treatments with three replications (10 chicks/replication) based on a completely randomized design. Diet was the same for all treatments but dried Spirulina powder (DSP) was provided in the feed as follows: control with no DSP (T5), 0.5% DSP (T1), 1% DSP (T2), 1.5 % DSP (T3) and antibiotic with no DSP (T4). Results: The results showed that the birds fed 0.5 and 1.5% DSP diets achieved superior body weights, body weight gain and feed conversion ratios compared to those of the control and antibiotic-treated groups. The weight of the lymphoid organ and internal organs of different groups showed that there was no significant (p>0.05) difference among the groups. The consequences of the biochemical test were also not significant (p>0.05) among the treatments. The results of the hematological studies showed no significant (p>0.05) differences due to supplementation of DSP, except for the number of red blood cells (RBC), number of lymphocytes and mean corpuscular hemoglobin concentration (MCHC) which all were significantly affected (p<0.05) compared with the control and antibiotic-treated groups. However, addition of DSP to the broiler chicksʼ diets showed significant (p<0.05) differences in the bacterial colony count among the groups. Conclusion: The results of this study demonstrate that Spirulina platensis supplementation positively affected the growth performance and health status in broilers, indicating that Spirulina platensis can be safely used to replace antibiotics as a growth promoter